Insulin-Loaded Barium Salt Particles Facilitate Oral Delivery of Insulin in Diabetic Rats - Rahela Zaman; Md. Emranul Karim; Iekhsan Othman; Anuar Zaini; Ezharul Hoque Chowdhury (MDPI AG, 2020)
Oral delivery is considered as the most preferred and yet most challenging mode of drug administration; especially a fragile and sensitive peptide like insulin that shows extremely low bioavailability through the gastro-intestinal (GIT) route. To address this problem, we have designed a novel drug delivery system (DDS) using precipitation-induced Barium (Ba) salt particles. The DDS can load insulin molecules and transport them through the GIT route. There were several in vitro simulation tests carried out to prove the efficiency of Ba salt particles as oral delivery candidates. All three Ba salt particles (BaSO4, BaSO3, and BaCO3) showed very good loading of insulin (>70% in all formulations) and a degree of resistance throughout a wide range of pHs from basic to acidic conditions when assessed by spectrophotometry. Particles and insulin-associated particles were morphologically assessed and characterized using FE-SEM and FT-IR. A set of tests were designed and carried out with mucin to predict whether the particles are potentially capable of overcoming one of the barriers for crossing intestinal epithelium. The mucin binding experiment demonstrated 60-100% of mucin adhesion to the three different particles. FT-IR identifies the characteristic peaks for mucin protein, particles, and particle-mucin complex re-confirming mucin adhesion to the particles. Finally, the effectiveness of nano-insulin was tested on streptozotocin (STZ) induced diabetic rats. A short acting human insulin analog, insulin aspart, was loaded into Ba salt particles at a dose of 100 IU/Kg prior to oral administration. Among the three formulations, insulin aspart-loaded BaSO4 and BaCO3 particles dramatically reduced the existing hyperglycemia. BaSO4 with loaded Insulin showed an onset of glucose-lowering action within 1 hr, with blood glucose level measured significantly lower compared to the 2nd and 3rd h (p < 0.05). Insulin-loaded BaCO3 particles showed a significant decrease in blood glucose level at 1-2 h, although the glucose level started to show a slight rise at 3rd h and by 4th h, it was back to baseline level. However, although BaSO3 particles with loaded insulin showed a trend of reduction in blood glucose level, the reduction was not found to be significant (p < 0.05) at any point in time. Therefore, oral formulations of insulin/BaSO4 and insulin/BaCO3 particles were observed as effective as native insulin aspart subcutaneous formulation in terms of onset and duration of action. Further investigation will be needed to reveal bioavailability and mechanism of action of this novel Nano-Insulin formulations.